Effects of different mulching practices on soil microbial community structure, function, and interaction networks in a chieh-qua cultivation - Qiao, Yan-chun; Jiang, Xiao-xin; Zan, Jian-po; Chen, Xiao-hui; Liu, Feng; Zhang, Wen-sheng; He, Guo-ping; Peng, Jia-zhu; Wu, Yu-jun; Yang, Song-guang (Frontiers in Microbiology, 2026)
Background and aimsMulching is a widely used agricultural management practice with profound effects on soil properties and crop productivity. However, its impact on soil microbial community structure and function remains insufficiently understood. This study aimed to investigate how different mulching treatments influence the composition, functional potential, and interaction networks of soil microbial communities in a chieh-qua–legume rotation system.MethodsMetagenomic sequencing was employed to analyze soil samples subjected to four mulching treatments (biodegradable mulch, non-degradable silver mulch, non-degradable black mulch, and straw mulch) as well as a no-mulch control (CK).ResultsMulching treatments significantly altered soil microbial diversity and community structure, with straw and biodegradable mulches supporting higher diversity than the control. Biodegradable mulch was strongly correlated with changes in soil pH and enriched denitrifying bacteria such as Thauera and Comamonadaceae, while reducing the abundance of genes related to energy metabolism and carbon fixation. These findings suggest that organic carbon from mulch degradation may enhance denitrification, potentially leading to nitrogen loss. Co-occurrence network analysis revealed that biodegradable mulch promoted more complex and connected microbial networks, whereas plastic mulches resulted in simpler structures. Additionally, all mulching treatments significantly reduced the abundance of the autotrophic ammonia-oxidizing archaeon Thaumarchaeota, likely due to reduced soil oxygen under mulch.ConclusionThis study provides new insights into how different mulching practices modulate soil microbial communities and their ecological functions. The results underscore the importance of tailoring mulching strategies to maintain soil health and fertility. Specifically, nitrogen supplementation is recommended when using biodegradable mulch in chieh-qua cultivation systems.